Major Surgery in a Subject with Factor V Deficiency - Melliger, E. J; Duckert, F (Thrombosis and Haemostasis, 1971)
A further case of parahaemophilia is reported. One year after the correct diagnosis had been made the patient had to undergo cholecystectomy which was performed under prophylactic substitutive treatment with fresh plasma at a factor V level of 31 %. A minimal factor V level of 11 to 12% was maintained throughout the first week after operation. There was no abnormal postoperative bleeding. The half disappearance time of factor V was found to be about 12 h. Infusion of equivalent amounts of fresh plasma supplied a higher yield of factor V in the patient’s plasma before operation than postoperatively what may be explained by an increased diffusion of factor V into the intercellular space resulting from a postoperatively increased capillar permeability. The results are compared with those of other authors.